The territorialisation of the UN Agenda 2030 and crosscutting issues in energy, environment and health: The case of Portugal - Medeiros, E. (Sustainable policies and practices in energy, environment and health research: Addressing cross-cutting issues, 2022)
Sustainable policy transitions require a shift towards more collaborative societal values coupled with a sustainability supportive fiscal framework. The materialisation of sustainable policies and practices in the field of energy, the environment and health also require the establishment of building blocks for a more empowered, informed and vibrant civil society in addressing sustainable development challenges. Policymaking processes also need to follow participatory, subsidiarity and place-based governance principles (Barca 2009; Stead 2014). Moreover, eco-innovation practices can only succeed if all involved actors (SMEs and large companies, research institutions, consumers, etc.) proactively contribute to this transition towards a more sustainable territorial development pattern (Bontoux and Bengtsson 2015). Finally, the physical renovation of buildings to improve energy efficiency and the production of clean energy renders a tangible platform to materialise these intended sustainable policy transitions (Kanters and Wall 2014).